Meneropong Fenomena Beragama di Zaman Postmodernisme: Dari Ritual Kolektif ke Spiritualitas Individu - Priskardus Hermanto Candra (Indonesian Character Journal, 2026)
This paper examines fundamental changes in religious practice and understanding in the postmodern era, where collective religious authority has shifted toward a more personal form of spirituality. Postmodernism, as a critique of modernism and rationality that marginalizes human values, opens up space for pluralistic interpretations and individual spiritual freedom. Phenomena such as digital religion, the commodification of spirituality, and the emergence of alternative faith movements in Indonesia demonstrate that religious practices tend not to be closely tied to formal institutions, but rather to become reflective and subjective experiences. Using qualitative descriptive methods based on literature studies, this paper explores how contemporary religious patterns have evolved from collective rituals to individual spirituality, as well as their implications for social cohesion and the meaning of religiosity. The results show that this shift does not signal the decline of religion but rather a transformation toward a more dialogical, flexible form of religiosity that aligns with the existential needs of modern people.